2013
DOI: 10.1155/2013/123697
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reaction of Sn-Ag-Cu Lead-Free Solder Alloy on Cu: A Review

Abstract: This paper reviews the function and importance of Sn-Ag-Cu solder alloys in electronics industry and the interfacial reaction of Sn-Ag-Cu/Cu solder joint at various solder forms and solder reflow conditions. The Sn-Ag-Cu solder alloys are examined in bulk and in thin film. It then examines the effect of soldering conditions to the formation of intermetallic compounds such as Cu substrate selection, structural phases, morphology evolution, the growth kinetics, temperature and time is also discussed. Sn-Ag-Cu le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 60 publications
0
30
0
2
Order By: Relevance
“…In addition, the formation of large plate like Ag 3 Sn IMCs causes solid dissolution and precipitation hardening, which in turn decreases the matrix strength [54,55]. The overall reliability of the solder joint can be greatly affected by the amount and size of Ag 3 Sn IMCs in the microstructure [56]. Since the Cu content in the SAC-305 alloy is very small, the majority of the IMCs formed in SAC305 are Ag3Sn particles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the formation of large plate like Ag 3 Sn IMCs causes solid dissolution and precipitation hardening, which in turn decreases the matrix strength [54,55]. The overall reliability of the solder joint can be greatly affected by the amount and size of Ag 3 Sn IMCs in the microstructure [56]. Since the Cu content in the SAC-305 alloy is very small, the majority of the IMCs formed in SAC305 are Ag3Sn particles.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the results of microstructural examination using SEM on extruded CSES and CSI solder joints revealed no cracks or debonding at the interface which means the interfacial integrity was good (see Figures 13 and 15 bonding between the substrate and solder mostly depends on the integrity of the intermetallic compound (IMC) layer. e long-term reliability of solder joints depends on how, at the interface, IMCs are formed as reaction products between the solder and the substrate during soldering [38][39][40][41][42]. In this study, IMCs were clearly observed in Cu/ SAC305/Cu solder joints (see Figures 13(a) Figures 13(a), 13(c), 13(e), 13(g), 13(i), 13(k), 13(m), and 13(o)) had slightly less thickness than CSI (before and after corrosion) solder joints (see Figures 13(b), 13(d), 13(f ), 13(h), 13(j), 13(l), 13(n), and 13(p), which reduced the brittleness in CSES joints thus making CSES solder joints marginally better in strength than CSI solder joints.…”
Section: Microstructural Characterization Figures 12 and 13mentioning
confidence: 99%
“…Thick IMC negatively affect the long-term reliability of solder joints due to their brittle nature [4,5].…”
Section: Jointsmentioning
confidence: 99%